NHC-catalyzed allylation of aldehydes with MBH carbonates and their michael addition-elimination-cope rearrangement cascade: a route to rac-sacubitril - Kale, Tushar B.; Jagtap, Sayali G.; Mhaske, Santosh B. (Organic Letters, 2025)
We report herein a novel NHC-catalyzed transition-metal-free chemoselective allylation of aldehydes with Morita-Baylis-Hillman (MBH) carbonates using an inorganic base. Fascinatingly, the use of an organic base follows a different mechanism, leading to highly functionalized 1,5-dienes via a Michael addition-elimination reaction followed by [3,3]-sigmatropic Cope rearrangement. The described method harnesses a new Csp2-Csp3 bond to access alpha-methylene-gamma-oxo-gamma-substituted ester derivatives paving a way to facile synthesis of potent natural products and active pharmaceutical ingredients (APIs). A broad range of aromatic and aliphatic aldehydes with MBH carbonates was employed to provide a variety of interesting butanoate and dienyl ketone scaffolds in good to excellent yields. This chemistry has been extended to the efficient syntheses of rac-sacubitril API and gamma-butyrolactone scaffold, which is a privileged core present in many natural products and APIs

Organophotoredox-catalyzed decarboxylative C-O/N/S bond formation: access to ampakine APIs and quinazolinone alkaloids - Sonavane, Sameer R.; Kale, Tushar B.; Bhatt, Gaurang J.; Mhaske, Santosh B. (Organic Letters, 2025)
This study describes a novel and general protocol featuring organophotoredox-catalyzed intramolecular decarboxylative construction of carbon-heteroatom (oxygen, nitrogen, and sulfur) bonds, enabling direct access to ampakine APIs (CX-614 and CX-554), quinazolinone alkaloids (deoxyvasicinone and mackinazolinone), and thiazinone scaffolds as well as their congeners with broad functional group tolerance and scalability. Mechanistic studies suggest a radical-polar crossover pathway via single-electron oxidation.